Presentation of Biliary Ascariasis: A Study of 30 Cases - Begum, Hasina; Rahman, MM; Salahuddin, M; Ahmed, F; Hossain, A (Bangladesh Journal of Medicine, 2013)
DOI: http://dx.doi.org/10.3329/bjmed.v22i1.13593 Bangladesh J Medicine 2011; 22: 8-11